Maximizing farm resilience: the effect of climate smart agricultural adoption practices on food performance amid adverse weather events - Tunio, Raza Ali; Li, Dongmei; Khan, Nawab (Frontiers in Sustainable Food Systems, 2024)
Introduction: Global climate change (CC) significantly impacts sustainable food systems and the agricultural sector, primarily through increasing adverse weather events. This study aims to explore the adaptation strategies farmers use to address these challenges and evaluate the effectiveness of climate-smart agricultural (CSA) practices on food performance.We collected data from 720 crop farmers located in three provinces of Pakistan using a random sampling method. To address potential biases, this study employed the endogenous switching regression (ESR) model. This model effectively addresses endogeneity and selection bias by considering both observable and unobservable characteristics.Study findings indicate that CSA practices substantially enhance net farm returns, reduce volatility, and mitigate downside risks. The analysis also highlights key features affecting the acceptance of CSA practices, including higher education, age, climate information, and availability of agricultural extension services.Discussion: These insights are essential for policymakers, offering a framework for informed decision-making to tackle CC's effects on food production, improve living standards, and enhance global food security.